2014
DOI: 10.7566/jpsj.83.061016
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory for Plasmon-Assisted Superconductivity

Abstract: We review the recent progress in the density functional theory for superconductors (SCDFT). Motivated by the long-studied plasmon mechanism of superconductivity, we have constructed an exchange-correlation kernel entering the SCDFT gap equation which includes the plasmon effect. For the case of lithium under high pressures, we show that the plasmon effect substantially enhances the transition temperature (Tc) by cooperating with the conventional phonon mechanism and results in a better agreement between the th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 83 publications
1
47
0
1
Order By: Relevance
“…Several approximations for F xc have been proposed and tested [34, 263,264,235,265], and all lead to a BCS-like form of the equation above:…”
Section: Band Decoupling Approximationmentioning
confidence: 99%
“…Several approximations for F xc have been proposed and tested [34, 263,264,235,265], and all lead to a BCS-like form of the equation above:…”
Section: Band Decoupling Approximationmentioning
confidence: 99%
“…(23) is also useful to exclude the contribution to the electron-density modulation from the possible change in the Fermi energy in the case of q = 0 [the additional contribution given in Eqs. (11) and (12)]. The possible change in the Fermi energy originates from the intraband transitions at the Fermi level, which are the transition processes in the t-subspace and hence are excluded by employingβ n,m .…”
Section: A Basic Idea and Practical Implementationmentioning
confidence: 99%
“…Instead, if we had the equivalent of a BCS or Eliashberg theory at our disposal with a corresponding prediction of T c from the microscopic parameters, we could have arrived at a different conclusion. For example, it has been suggested, 131 for an s-wave superconductor, that a large on-site repulsion U can also increase T c in the frequency region where the gap function becomes negative since, then, the product between U and the gap leads to an effective attractive interaction. Nevertheless, even if one could expect the same thing to happen with V , here we found that at infinite frequency, V is definitely pair-breaking.…”
Section: Pairing Mechanism Retardation and Gluementioning
confidence: 99%